2014
DOI: 10.1103/physreva.90.024304
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement monogamy relations of qubit systems

Abstract: We investigate the monogamy relations related to the concurrence and the entanglement of formation. General monogamy inequalities given by the αth power of concurrence and entanglement of formation are presented for N -qubit states. The monogamy relation for entanglement of assistance is also established. Based on these general monogamy relations, the residual entanglement of concurrence and entanglement of formation are studied. Some relations among the residual entanglement, entanglement of assistance and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
201
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(205 citation statements)
references
References 29 publications
1
201
2
Order By: Relevance
“…However, there exists a kind of three-qubit mixed states which is entangled but without two-qubit concurrence and three-tangle [38], and the similar case also exists in Nqubit systems [39]. Recently, it was indicated that the squared entanglement of formation (SEF) [3] obeys the monogamy relation in multiqubit systems [40][41][42][43][44][45]. In particular, it was which overcomes the flaw of the MoE of SC and can be utilized to detect all multiqubit entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…However, there exists a kind of three-qubit mixed states which is entangled but without two-qubit concurrence and three-tangle [38], and the similar case also exists in Nqubit systems [39]. Recently, it was indicated that the squared entanglement of formation (SEF) [3] obeys the monogamy relation in multiqubit systems [40][41][42][43][44][45]. In particular, it was which overcomes the flaw of the MoE of SC and can be utilized to detect all multiqubit entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, EOF itself does not satisfy the usual monogamy rela- * Electronic address: ykbai@semi.ac.cn † Electronic address: zwang@hku.hk tion even for three-qubit pure states. Recently, it was indicated that the squared entanglement of formation (SEF) obeys the monogamy relation in multiqubit systems [30][31][32][33]. In particular, we proved analytically that the SEF is monogamous in an arbitrary N -qubit mixed state and obeys the relation [32] …”
Section: Introductionmentioning
confidence: 84%
“…Monogamy relations are not always satisfied by entanglement measures. Although the concurrence and entanglement of formation do not satisfy such monogamy inequality, it has been shown that the αth (α ≥ 2) power of concurrence and αth (α ≥ √ 2) power entanglement of formation for N -qubit states do satisfy the monogamy relations [8].In this paper, we study the general monogamy inequalities satisfied by the concurrence and concurrence of assistance. We show that the concurrence of multi-qubit pure states satisfies some generalized monogamy inequalities.…”
mentioning
confidence: 95%
“…Monogamy relations are not always satisfied by entanglement measures. Although the concurrence and entanglement of formation do not satisfy such monogamy inequality, it has been shown that the αth (α ≥ 2) power of concurrence and αth (α ≥ √ 2) power entanglement of formation for N -qubit states do satisfy the monogamy relations [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation